A Case of Kikuchi’s Disease Presenting with Fever and Lymphadenopathy (TAJ: Journal of Teachers Association, 2018)
Kikuchi’s disease is a rare, benign, self-limiting disorder, characterized clinically by fever and regional lymphadenopathy. Histopathologic features of lymph nodes in Kikuchi’s disease are characteristic and permit differentiation of this benign condition from lymphomas, systemic lupus erythematosus and infectious lymphadenopathies. We report a female patient presenting with fever and tender cervical lymphadenopathy. An excisional biopsy of the lymph node reveale lymphadenitis, consistent with Kikuchi’s disease.TAJ 2012; 25: 81-83